La centralité du foncier dans le régime d’accumulation du capital en Chine - Natacha Aveline-Dubach (Revue de la Régulation)
This paper engages in a discussion between regulationists and urban scientists with the aim of bringing awareness of the growing role of property markets as drivers of contemporaneous capitalist regimes — a dimension that has not been given sufficient consideration by the French Regulation School. The case of China exemplifies the centrality of land in macroeconomic dynamics. This paper explores this centrality trough the prism of the Development State (DS), a framework that sets China’s experience in the broader context of Northeast Asia. Three main characteristics of Johnson’s DS framework (1982) are mobilized to highlight the role of property value enhancement in the regime of capital accumulation in China, i.e. the primary focus on GDP growth, state control over capital allocation to the economy, and manifestations of economic nationalism. It is argued that the Chinese state — at both central and local level — has used the mechanism of property value enhancement as a major tool to ensure a smoother economic transition, by encouraging residential investment as a quasi exclusive saving vehicle. Selective strategies in banking credit allocation and restrictions to the development of financial markets, both aiming to maintain state’s stranglehold over financial supply to the productive base, have generated the proliferation of a poorly monitored "grey finance" mainly collateralized by land. To keep control over the land rent and ensure its adequate appropriation by domestic players, the state has dramatically restricted foreign inflows of capital in China’s property markets, and at the same time,  has encouraged outbond investment in real estate to alleviate pressure on saving demand by domestic players. These findings highlight the pivotal role of land/property markets in the construction of fundamental institutional forms defined by the Regulation framework.